Nutritional and motor ability status of first- and second- grade students - Živan Milošević; Dejan Čokorilo; Nikola Pajić; Višnja Đorđić (University of Novi Sad, Faculty of Sport and Physical Education, 2018)
Abstract Nutritional status is a relevant indicator of optimal growth and development, as well as the health status of children. Since nutritional status can influence the expression of children's motor capacities, a study has been carried out in order to examine differences in motor abilities of children in relation to their nutritional status. The sample included 300 first- and second-grade students (132 boys, 168 girls). Students' motor literacy and motor ability status was evaluated by reduced version of "EUROFIT" test battery, while nutritional status was evaluated based on the body mass index. IOTF criteria were used in order to assign participants into four distinctive groups - underweight, normal weight, overweight and obese. Differences between groups in motor ability status were tested by Kruskal-Wallis and Mann-Whitney tests. No significant differences were found between groups of a different nutritional status in most of the motor abilities, suggesting that BMI does not represent a high-quality predictor of motor abilities of children of lower elementary school grades.